equal roots
discriminant = 0 (b^2-4ac, a = 1 b = -m . c = 4)
m^2 - 4*4 = 0 or m= 4 or -4
m = 4 means ^2-4x+4 = 0 oots are 2 and 2
m = -4 means ^2+4x+4 = 0r roots 2 and -2
roots are real as well
refer to https://in.answers.yahoo.com/question/index?qid=20111021024215AACQbhH
some short and selected math problems of different levels in random order I try to keep the ans simple
Tuesday, December 23, 2014
Monday, December 22, 2014
2014/115) how many factors of 240 are therer which are of the form 4n+ 2
240 can be factored as 2^4 * 3 * 5
now for a factor to be of the form it should be 2 multiplied by by an odd number,
so it is 1 * (1+1) * (1+1) ( one way of choosing 2, 2 ways of choosing power of 3 ( 3^0, 3^1) and same way 2 ways of choosing 5) or it is 4
now for a factor to be of the form it should be 2 multiplied by by an odd number,
so it is 1 * (1+1) * (1+1) ( one way of choosing 2, 2 ways of choosing power of 3 ( 3^0, 3^1) and same way 2 ways of choosing 5) or it is 4
Sunday, December 21, 2014
2014/114) solve the equation (x-3)^4 + (x-7)^4 = 24832
Before I provide the solution I would like to mention that generally a quartic polynomial is not easy to solve but this type of equation
(x-a)^4 + (x-b)^4= c can be converted to a quadratic equation by transformation of
y= \dfrac{(x-a) + (x-b)}{2}
as below
we shall put
y= \dfrac{(x-3) + (x-7)}{2} = x- 5
so we get
(y+2)^4 + (y-2)^4 = 24832
or 2(y^4 + 6 y^2 (-2)^2 + 16) = 24832
or y^4 + 24 y^2 = 12400
y^4 + 24 y^2 – 12400 = 0
or (y^2 – 100)(y^2 + 124) = 0
so y^2 = 100
so y = \pm 10
or x = -5 or 15
(x-a)^4 + (x-b)^4= c can be converted to a quadratic equation by transformation of
y= \dfrac{(x-a) + (x-b)}{2}
as below
we shall put
y= \dfrac{(x-3) + (x-7)}{2} = x- 5
so we get
(y+2)^4 + (y-2)^4 = 24832
or 2(y^4 + 6 y^2 (-2)^2 + 16) = 24832
or y^4 + 24 y^2 = 12400
y^4 + 24 y^2 – 12400 = 0
or (y^2 – 100)(y^2 + 124) = 0
so y^2 = 100
so y = \pm 10
or x = -5 or 15
2014/113) find the number of solutions of \sin\,x = \dfrac{x}{100}
first let us look at positive x and same number of solutions shall be for -ve x
as \sin,x and x both are odd functions.
as \sin\,x is less than 1 so x shall be less than 100 and so if we draw a sin curve there shall be \dfrac{100}{2\pi} or 15.91 ( around 16) units so there shall be 16 parts( 1/2 oscilaltions) in positive side and 16 in -ve side.
for each on the curve y = x shall intersect the sin curve 2 times so 32 in positive side including zero) so there is 1 value at 0, 31 positive values and 31 -ve values or 63 values
as \sin,x and x both are odd functions.
as \sin\,x is less than 1 so x shall be less than 100 and so if we draw a sin curve there shall be \dfrac{100}{2\pi} or 15.91 ( around 16) units so there shall be 16 parts( 1/2 oscilaltions) in positive side and 16 in -ve side.
for each on the curve y = x shall intersect the sin curve 2 times so 32 in positive side including zero) so there is 1 value at 0, 31 positive values and 31 -ve values or 63 values
2014/112) if x+y is divisble by 3 show that x^3+y^3 is divisible by 9
we have
x^3+y^3= (x+y)^3 - 3xy(x+y)
if (x+y) is divisible by 3 then (x+y)^3 is divisible by 9 ( it is divisible by 27 but 9 is required) and 3xy(x+y) is divisible by 9 and hence the difference.
x^3+y^3= (x+y)^3 - 3xy(x+y)
if (x+y) is divisible by 3 then (x+y)^3 is divisible by 9 ( it is divisible by 27 but 9 is required) and 3xy(x+y) is divisible by 9 and hence the difference.
Saturday, December 20, 2014
2014/111) Show that the function below has same remainder when divided by x(x+1) and x(x+1)^2
f(x)=2008+2007x+2006x^2+\cdots+3x^{2005}+2x^{2006}+x^{2007}
1st we provide the premise
this shall have same remainder when divided by x(x+1) and x(x+1)^2
provided this shall have same remainder when divided by (x+1) and (x+1)^2
when we divide by (x+1)^2 we shall have a linear polynomial say m(x+1) + c and when we divide by (x+1) it shall be d and both are same if m= 0 and m+c = d
so if we convert
f(x) as a polynomial of (x+1) the coefficient of x should be zero
of f(x-1) should have coefficient of x to be zero
now we provide the solution based on premise
f(x-1)=2008+2007(x-1)+2006(x-1)^2+\cdots
+3(x-1)^{2005}+2(x-1)^{2006}+(x-1)^{2007}
should have coefficient of x to be zero
the coefficient of x
= 2007 + 2006 * (-2) + 2005 * 3 \cdots + 2 * 2006 - 2007 = 0
hence proved
I have solved the problem at http://mathhelpboards.com/challenge-questions-puzzles-28/division-polynomial-13760.html#post65389 where you can find some more different solutions
1st we provide the premise
this shall have same remainder when divided by x(x+1) and x(x+1)^2
provided this shall have same remainder when divided by (x+1) and (x+1)^2
when we divide by (x+1)^2 we shall have a linear polynomial say m(x+1) + c and when we divide by (x+1) it shall be d and both are same if m= 0 and m+c = d
so if we convert
f(x) as a polynomial of (x+1) the coefficient of x should be zero
of f(x-1) should have coefficient of x to be zero
now we provide the solution based on premise
f(x-1)=2008+2007(x-1)+2006(x-1)^2+\cdots
+3(x-1)^{2005}+2(x-1)^{2006}+(x-1)^{2007}
should have coefficient of x to be zero
the coefficient of x
= 2007 + 2006 * (-2) + 2005 * 3 \cdots + 2 * 2006 - 2007 = 0
hence proved
I have solved the problem at http://mathhelpboards.com/challenge-questions-puzzles-28/division-polynomial-13760.html#post65389 where you can find some more different solutions
Monday, December 15, 2014
2014/110) Find closed form of
\cos\,1^\circ \cos\,2^\circ + \cos\,2^\circ \cos\,3^\circ\cdots \cos\,88^\circ \cos\,89^\circ
we have 2 \cos(x) \cos (y) = \cos (x+y) + \cos (y-x)
so 2 (\cos\,1^\circ \cos\,2^\circ ) = \cos\,3^\circ + \cos\,1^\circ
2 (\cos\,2^\circ \cos\,3^\circ ) = \cos\,5^\circ + \cos\,1^\circ
so on till
2 (\cos\,44^\circ \cos\,45^\circ ) = \cos\,89^\circ + \cos\,1^\circ
2 (\cos\,45^\circ\cos\,46^\circ ) = \cos\,91^\circ + \cos\,1^\circ
or 2 (\cos\,45^\circ \cos\,46^\circ ) = - \cos\,89^\circ + \cos\,1^\circ
so on till
2 (\cos\,88^\circ \cos\,89^\circ ) = - \cos\,3^\circ + \cos\,1^\circ
on adding above for each positive term in 1st half for the first term there is a -ve term for the second half and we are left wth 88 times \cos\,1^\circ
so 2( \cos\,1^\circ \cos\,2^\circ + (\cos\,2^\circ \cos\,3^\circ +\cdots \cos\,88^\circ \cos\,89^\circ) = 88 \cos\,1^\circ
or ( \cos\,1^\circ \cos\,2^\circ + (\cos\,2^\circ \cos\,3^\circ +\cdots \cos\,88^\circ \cos\,89^\circ) = 44 \cos\,1^\circ
we have 2 \cos(x) \cos (y) = \cos (x+y) + \cos (y-x)
so 2 (\cos\,1^\circ \cos\,2^\circ ) = \cos\,3^\circ + \cos\,1^\circ
2 (\cos\,2^\circ \cos\,3^\circ ) = \cos\,5^\circ + \cos\,1^\circ
so on till
2 (\cos\,44^\circ \cos\,45^\circ ) = \cos\,89^\circ + \cos\,1^\circ
2 (\cos\,45^\circ\cos\,46^\circ ) = \cos\,91^\circ + \cos\,1^\circ
or 2 (\cos\,45^\circ \cos\,46^\circ ) = - \cos\,89^\circ + \cos\,1^\circ
so on till
2 (\cos\,88^\circ \cos\,89^\circ ) = - \cos\,3^\circ + \cos\,1^\circ
on adding above for each positive term in 1st half for the first term there is a -ve term for the second half and we are left wth 88 times \cos\,1^\circ
so 2( \cos\,1^\circ \cos\,2^\circ + (\cos\,2^\circ \cos\,3^\circ +\cdots \cos\,88^\circ \cos\,89^\circ) = 88 \cos\,1^\circ
or ( \cos\,1^\circ \cos\,2^\circ + (\cos\,2^\circ \cos\,3^\circ +\cdots \cos\,88^\circ \cos\,89^\circ) = 44 \cos\,1^\circ
Sunday, December 14, 2014
problem 2014/109) prove that \dfrac{\sin\,x - \cos\, x + 1}{\sin\, x + \cos\, x – 1} = \dfrac{1 + \tan \frac{x}{2}}{1- \tan\frac{x}{2}}
Proof
convert it into \dfrac{x}{2} form
numerator = 2 sin \dfrac{x}{2}\cos\dfrac{x}{2} + 2 \sin ^2\dfrac{x}{2} (as \cos\, x= 1 - 2 \sin ^2 \dfrac{x}{2}) = 2 \sin \dfrac{x}{2}( \cos \dfrac{x}{2} + \sin \dfrac{x}{2})
denominator = 2 \sin \dfrac{x}{2} \cos \dfrac{x}{2} - 2 \cos^2 \dfrac{x}{2} (as cos\, x= 2 \cos^2 \dfrac{x}{2} - 1 = 2 \sin \dfrac{x}{2}(\cos \dfrac{x}{2}- \sin \dfrac{x}{2})
dividing
we get
\dfrac{\sin\,x - \cos\,x + 1}{\sin\,x + \cos\,x - 1} = \dfrac{\cos \dfrac{x}{2} + \sin \dfrac{x}{2}}{\cos\dfrac{x}{2}-\sin \dfrac{x}{2}}
= \dfrac{(1 + \tan \dfrac{x}{2})\cos\dfrac{x}{2}}{(1 - \tan \dfrac{x}{2})\cos\dfrac{x}{2}}
= \dfrac{1 + \tan \dfrac{x}{2}}{(1 - \tan \dfrac{x}{2}}
convert it into \dfrac{x}{2} form
numerator = 2 sin \dfrac{x}{2}\cos\dfrac{x}{2} + 2 \sin ^2\dfrac{x}{2} (as \cos\, x= 1 - 2 \sin ^2 \dfrac{x}{2}) = 2 \sin \dfrac{x}{2}( \cos \dfrac{x}{2} + \sin \dfrac{x}{2})
denominator = 2 \sin \dfrac{x}{2} \cos \dfrac{x}{2} - 2 \cos^2 \dfrac{x}{2} (as cos\, x= 2 \cos^2 \dfrac{x}{2} - 1 = 2 \sin \dfrac{x}{2}(\cos \dfrac{x}{2}- \sin \dfrac{x}{2})
dividing
we get
\dfrac{\sin\,x - \cos\,x + 1}{\sin\,x + \cos\,x - 1} = \dfrac{\cos \dfrac{x}{2} + \sin \dfrac{x}{2}}{\cos\dfrac{x}{2}-\sin \dfrac{x}{2}}
= \dfrac{(1 + \tan \dfrac{x}{2})\cos\dfrac{x}{2}}{(1 - \tan \dfrac{x}{2})\cos\dfrac{x}{2}}
= \dfrac{1 + \tan \dfrac{x}{2}}{(1 - \tan \dfrac{x}{2}}
2014/108) Find the remainder when 2^{1990} is divided by 1990
We have 1990 = 10*199 = 2* 5* 199
now we have
2^4 mod 5 = 1 as per fermat theorem
so 2^{1990} mod 5 = 2^2 mod 5 = 4 mod 5
2^{ 198} = 1 mod 199
so 2^{1990} mod 199 = 2^10 mod 199 = 1024 mod 199 = 29 mod 199
2^{1990} mod 2 = 0
so 2^{ 1990} mod 199 = 29
2^{1990} mod 5 = 4
using Chinese Remainder Theorem you can proceed
continuing further
2^{1990} = 0 mod 2
2^{1990} = 4 mod 5
this gives 2^{1990} = 4 mod 10
now using
a = 4 (mod\, 10)
a = 29 (mod\, 199)
Notice that 20*10+(-1)*199=1, thus 20*10≡1 (mod 199) and -199≡1 (mod 10)
let a= 29*(20•10)+4*(-199), then it is clear that
a = 29*(0)+4*(1)=4 (mod 10) and a=29•(1)+4•(0)=29 (mod 199) so this a works for what we want.
a= 5004=1024 (mod 1990)
so the remainder is 1024
Sunday, December 7, 2014
Q2014/107) find coefficient of a^2 in the following expression
(1-a^2)+(1-a^2)^2+(1-a^2)^3+(1-a^2)^4+(1-a^2)^5+(1-a^2)^6
+(1-a^2)^7+(1-a^2)^8+(1-a^2)^9+(1-a^2)^{10}+(1-a^2)^{11}+(1-a^2)^{12}
if we put x= (1-a^2)
we get given expression as
x+x^2+x^3+x^4+x^5+x^6+x^7+x^8+x^9+x^{10}+x^{11}+x^{12}= x\dfrac{1-x^{12}}{1-x}
= (1-a^2)\dfrac{1-(1-a^2)^{12}}{a^2}
= \dfrac{(1-a^2)-(1-a^2)^{13}}{a^2}
now \dfrac{1-a^2}{a^2} shall not contribute to a^4 so we need to find the coefficient of a^6 in -(1-a^2)^{13} which is {13\choose 3}
that is the ans
+(1-a^2)^7+(1-a^2)^8+(1-a^2)^9+(1-a^2)^{10}+(1-a^2)^{11}+(1-a^2)^{12}
if we put x= (1-a^2)
we get given expression as
x+x^2+x^3+x^4+x^5+x^6+x^7+x^8+x^9+x^{10}+x^{11}+x^{12}= x\dfrac{1-x^{12}}{1-x}
= (1-a^2)\dfrac{1-(1-a^2)^{12}}{a^2}
= \dfrac{(1-a^2)-(1-a^2)^{13}}{a^2}
now \dfrac{1-a^2}{a^2} shall not contribute to a^4 so we need to find the coefficient of a^6 in -(1-a^2)^{13} which is {13\choose 3}
that is the ans
2014/106) find sum of real roots of the following
2x^8-9x^7+20x^6-33x^5+46x^4-66x^3+80x^2-72x+32=0
we have
2x^8-9x^7+20x^6-33x^5+46x^4-66x^3+80x^2-72x+32=0
= 2(x^8+ 16) -9(x^7+8x) +20(x^6+ 4x^2) -33(x^5+2x^3) + 46x^4=0
or deviding by x^4 as x = 0 is not a solution we get
2(x^4 + (\dfrac{2}{x})^4)-9(x^3 + (\dfrac{2}{x})^3)+20((x^2 + (\dfrac{2}{x})^2)-33(x (+\dfrac{2}{x}))+46 = 0
now if we put x+\dfrac{2}{x}=t
we get
x^2+(\dfrac{2}{x})^2=t^2-4
x^3+(\dfrac{2}{x})^3=t^3-6t
x^4+(\dfrac{2}{x})^4=t^4-8t + 8
so given relation reduces to
2(t^2-8t^2 +8) -9(t^3-6t) +20(t^2-4) - 33t + 46= 0
or 2t^4-9t^3+4t^2+21t-18=0
now we see that t = 1 and t = 3 are solutions and hence we get
2t^4-9t^3+4t^2+21t-18=0
= 2t^3(t-1) - 7t^2(t-1) -3t(t-1) + 18(t-1)=0
or(t-1)(2t^3-7t^2-3t+18) = 0
gives a solution t = 1
or
2t^3-7t^2- 3t + 18 = 0 as 3 is a root we get
2t^2(t-3) - t(t-3) - 6(t-3) = 0
or (t-3)(2t^2 - t^2-3) = 0
so t = 3
or 2t^2 - t - 3 = 0
or (2t-3)(t+1) = 0
so t = 1 or 3 or - 1 or -\dfrac{3}{2}
now t = x+ \dfrac{2}{x} and if x is positive then by AM GM inequality lowest value = 2\sqrt{2}
or only possible value from above is
t = 3 (as t cannot be between -2\sqrt{2} and 2\sqrt{2})
t = 3 gives x = 1 or 2 and so sum of real roots = 3
I had the privilege to solve it at http://mathhelpboards.com/challenge-questions-puzzles-28/find-sum-real-roots-13522.html#post64344
we have
2x^8-9x^7+20x^6-33x^5+46x^4-66x^3+80x^2-72x+32=0
= 2(x^8+ 16) -9(x^7+8x) +20(x^6+ 4x^2) -33(x^5+2x^3) + 46x^4=0
or deviding by x^4 as x = 0 is not a solution we get
2(x^4 + (\dfrac{2}{x})^4)-9(x^3 + (\dfrac{2}{x})^3)+20((x^2 + (\dfrac{2}{x})^2)-33(x (+\dfrac{2}{x}))+46 = 0
now if we put x+\dfrac{2}{x}=t
we get
x^2+(\dfrac{2}{x})^2=t^2-4
x^3+(\dfrac{2}{x})^3=t^3-6t
x^4+(\dfrac{2}{x})^4=t^4-8t + 8
so given relation reduces to
2(t^2-8t^2 +8) -9(t^3-6t) +20(t^2-4) - 33t + 46= 0
or 2t^4-9t^3+4t^2+21t-18=0
now we see that t = 1 and t = 3 are solutions and hence we get
2t^4-9t^3+4t^2+21t-18=0
= 2t^3(t-1) - 7t^2(t-1) -3t(t-1) + 18(t-1)=0
or(t-1)(2t^3-7t^2-3t+18) = 0
gives a solution t = 1
or
2t^3-7t^2- 3t + 18 = 0 as 3 is a root we get
2t^2(t-3) - t(t-3) - 6(t-3) = 0
or (t-3)(2t^2 - t^2-3) = 0
so t = 3
or 2t^2 - t - 3 = 0
or (2t-3)(t+1) = 0
so t = 1 or 3 or - 1 or -\dfrac{3}{2}
now t = x+ \dfrac{2}{x} and if x is positive then by AM GM inequality lowest value = 2\sqrt{2}
or only possible value from above is
t = 3 (as t cannot be between -2\sqrt{2} and 2\sqrt{2})
t = 3 gives x = 1 or 2 and so sum of real roots = 3
I had the privilege to solve it at http://mathhelpboards.com/challenge-questions-puzzles-28/find-sum-real-roots-13522.html#post64344
Subscribe to:
Posts (Atom)